Let's start by solving the equation:
\[ -x^2 - 3x = 5 - 3x \]
First, let's move all terms to one side of the equation:
\[ -x^2 - 3x + 3x - 5 = 0 \]
This simplifies to:
\[ -x^2 - 5 = 0 \]
Next, we can multiply the entire equation by -1 to make it easier to work with:
\[ x^2 + 5 = 0 \]
Now, we isolate \(x^2\):
\[ x^2 = -5 \]
Taking the square root of both sides gives us:
\[ x = \pm \sqrt{-5} \]
This can be expressed using the imaginary unit \(i\):
\[ x = \pm \sqrt{5}i \]
Thus, the solutions to the equation are:
\[ x = \sqrt{5}i \quad \text{and} \quad x = -\sqrt{5}i \]
Re-expressing the answer as a complex number with the imaginary unit gives:
\[ x = 0 \pm \sqrt{5}i \]
So the final answer is:
\[ x = \sqrt{5}i \quad \text{and} \quad x = -\sqrt{5}i \]